Determination of Trace Mercury in Cosmetics by Suspension- Sampling Hydride Generation Atomic Fluorescence Spectrometry - Liu, Shipeng; Zhang, Pingping; Liu, Hongchao; Wang, Wei; Lian, Kaoqi (Asian Journal of Chemistry, 2013)
A method has been developed for the determination of mercury in cosmetics by suspension-sampling hydride generation atomic fluorescence spectrometry. About 500 mg cosmetics, was mixed with absolute ethanol and agar solution. The samples were agitated with a vortex for 10 min. The procedure permits the use of direct calibration for the determination of mercury in several cosmetic samples. The influences of instrument operating conditions, suspension preparation and interferences on the signals and the accuracy and precision were determined. The results for the reference cosmetic sample GBW09303a agreed satisfactorily with the certified values. The recoveries of the analytes varied in the range from 94 to 106 %. The detection limit was 2.4 ng L-1 of Hg. The relative standard deviations were lower than 4.2 %, demonstrating a good precision for slurry analysis.